2014
DOI: 10.1590/s0036-46652014000300003
|View full text |Cite
|
Sign up to set email alerts
|

RESISTANCE TO AMOXICILLIN, CLARITHROMYCIN AND CIPROFLOXACIN OF Helicobacter pylori ISOLATED FROM SOUTHERN BRAZIL PATIENTS

Abstract: Introduction: Helicobacter pylori is a bacteria which infects half the world population and is an important cause of gastric cancer. The eradication therapy is not always effective because resistance to antimicrobials may occur. The aim of this study was to determine the susceptibility profile of H. pylori to amoxicillin, clarithromycin and ciprofloxacin in the population of Southern Brazil. Material and methods: Fifty four samples of H. pylori were evaluated. The antibiotics susceptibility was determined acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
(32 reference statements)
5
17
1
Order By: Relevance
“…H. pylori shows varied antibiotic susceptibility patterns in various geographical locations; moreover, this bacterium has been substantially influenced by the prior use of these drugs (Han et al, 1999). Previous studies conducted in Brazil have reported varying rates of H. pylori resistance to clarithromycin, ranging from 11.1 to 17.3% (Prazeres Magalhães et al, 2002;Eisig et al, 2011;Picoli et al, 2014). In this study, we could not show an association between the CYP2C19 genotype and efficacy of H. pylori eradication; however, H. pylori eradication was observed in a large proportion of patients (87.2%).…”
Section: Discussioncontrasting
confidence: 77%
“…H. pylori shows varied antibiotic susceptibility patterns in various geographical locations; moreover, this bacterium has been substantially influenced by the prior use of these drugs (Han et al, 1999). Previous studies conducted in Brazil have reported varying rates of H. pylori resistance to clarithromycin, ranging from 11.1 to 17.3% (Prazeres Magalhães et al, 2002;Eisig et al, 2011;Picoli et al, 2014). In this study, we could not show an association between the CYP2C19 genotype and efficacy of H. pylori eradication; however, H. pylori eradication was observed in a large proportion of patients (87.2%).…”
Section: Discussioncontrasting
confidence: 77%
“…This is in agreement with most of the local and international studies which reported rates that are similar to our results However, the reported MIC values of clarithromycin resistant H. pylori in our study were higher. [38,39]. In a study conducted by PCR for the detection of point mutations associated with clarithromycin resistance, similar rates were reported in Jordan [31].…”
supporting
confidence: 60%
“…In addition, the MIC values where less than 0.125 µg/ ml indicating that amoxicillin is a good choice of antimicrobial agents that should be included in the treatment regimens for H. pylori. In Brazil, resistance to amoxicillin has been detected in 29% of strains recovered from post-treatment [39]. However, many studies from other countries have shown that all strains examined are susceptible to amoxicillin [42,43].…”
mentioning
confidence: 99%
“…Many studies on H. pylori primary antibiotic resistance rates were carried out over the last year. They are summarized in Table 1 [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Although molecular in vitro testing gives a genotype that may not correspond to the phenotype in vivo, broad themes that do emerge are the increasing rates of clarithromycin and also fluoroquinolone resistance.…”
Section: Antimicrobial Resistancementioning
confidence: 99%